Identitas Gereja Genetik dari Israel: Sebuah Kritik Poskolonial Terhadap Wacana “Saudara Seiman” - Risno Tampilang (Institut Agama Kristen Negeri Palangka Raya, 2024)
The Israeli-Palestinian conflict has had a global impact, including in Indonesia, with the emergence of the discourse of “brothers in faith” which has the potential to increase tensions. This study proposes the thesis that this discourse in the New Testament needs to be re-examined through a postcolonial perspective, because it has the potential to perpetuate colonialism based on the genetic linkage of identity. The aim is to conduct a postcolonial critique of the understanding that is too Israel-centric and to develop a more inclusive theology. Methodologically, this study uses a descriptive qualitative study and a postcolonial approach. The results of the analysis show that the historical and theological ties between Christians and Jews/Israel often lead to uncritical support for modern Israeli policies. The church needs to deconstruct exclusive understandings and develop a more balanced perspective on contemporary understandings. In conclusion, the church must shift from exclusive identity to an inclusive-humanist understanding as an agent of transformation that fights for justice for all parties. Further research is recommended to explore the practical implementation of this inclusive theology in the context of the local church.